DIFFERENTIAL AND DIAGNOSTIC CRITERIA FOR HYPERMOBILITY OF THE ARTICULAR HEADS OF THE MANDIBLE, MUSCLE AND JOINT CONTRACTURE AND COMPRESSION-DISLOCATION DYSFUNCTION OF TEMPOROMANDIBULAR JOINT (ACCORDING TO THE DATA OF TMJ ZONOGRAPHY) - Yatsenko, P.I.; Yatsenko, O.I.; Rybalov, O.V.; Ivanytska, O.S.; Novikov, V.M. (World of Medicine and Biology, 2018)
The article deals with the results of systematic visual analysis of the TMJ zonograms of 67 patients with compression-dislocation dysfunction of TMJ, 29 patients with hypermobility of the articular heads of the mandible and 12 patients with a muscle and joint unilateral contracture of the mandible. The obtained data not only expand the scientific understanding of the pathogenesis of the aforementioned dysfunctions of TMJ, but also have practical significance for their more accurate differential diagnosis and ensuring adequate treatment of patients.